Evaluation of Astigmatism-Correcting Efficiency and Rotational Stability after Cataract Surgery with a Double-Loop Haptic Toric Intraocular Lens: A 1-Year Follow-Up - Nováček, Ladislav Viktor; Němcová, Marie; Tyx, Kateřina; Lahodová, Kristýna; Rejmont, Leoš; Rozsíval, Pavel; Studený, Pavel (Biomedicine hub, 2021)
OBJECTIVES: The aim of this study was to assess the clinical outcomes, predictability of results, efficiency of astigmatism correction, and rotational stability of the Bi-Flex 677TAY (Medicontur Medical Engineering Ltd., Zsámbék, Hungary) monofocal toric intraocular lens (IOL) designed for cataract patients with astigmatism. METHODS: The IOLs were implanted either mono- or binocularly, following routine cataract surgery. Visual and refractive outcomes, as well as off-axis rotation were assessed throughout a 1-year follow-up period. All clinical data for this work were collected retrospectively. Vector analysis based on the Alpins method was performed to assess the efficiency of astigmatism correction. RESULTS: No complications or adverse events occurred during surgery or the follow-up period. IOL implantation brought 88% of eyes into the ±0.50 D, and 100% into the ± 1.00 D range compared to the target spherical equivalent refraction, emmetropia. Astigmatism correction brought similar results: 94% of eyes had a residual cylindrical error of not higher than ±0.50 D, and 97% were within ±1.00 D. Vector analysis resulted in a correction index of 0.96 and a difference vector of 0.17. Both refractive and visual outcomes showed long-term stability. During the 12-month follow-up period, no eyes had a rotation of >5°. Absolute rotation after 1 year was 1.42 ± 1.89° (median = 0°), while signed rotation was 1.06 ± 2.12° (median = 0°). CONCLUSION: The Bi-Flex 677TAY monofocal toric IOL, designed by Medicontur Medical Engineering Ltd., represents an efficient and safe solution for cataract patients with astigmatism. Clinical and refractive outcomes are predictable, and rotational stability ensures long-term visual comfort.
Keywords: Cataract; Rotational stability; Astigmatism correction; Intraocular lens; Toric lens